Application Of Signed Graph In Decision Making - Pal, Anita; Banerjee, Debanjan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
A signed graph may be defined as an ordered pair (G, σ) where G= (V, E) is the graph and σ is a function called signature or sign mapping from E to the sign group {+, -}. People or friends are considered as the vertices and the relationships between these friends are considered as the edges. '+' sign is assigned to the edge for good relationship and '-' sign for bad relationship between the friends. Two terms friendship matrix or “judgement matrix and character point C.P are introduced in this paper. Using the concept of friendship matrix and C.P in various fields the characteristics or performances could be evaluated. In this paper different problems have been considered and analysed with the help of signed graph.